Answer:
SEE BELOW
Explanation:
to understand this
you need to know about:
let's solve:
vertex:(h,k)
therefore
vertex:(-1,4)
axis of symmetry:x=h
therefore
axis of symmetry:x=-1
- to find the quadratic equation we need to figure out the vertex form of quadratic equation and then simply it to standard form i.e ax²+bx+c=0
vertex form of quadratic equation:
therefore
- y=a(x-(-1))²+4
- y=a(x+1)²+4
it's to notice that we don't know what a is
therefore we have to figure it out
the graph crosses y-asix at (0,3) coordinates
so,
3=a(0+1)²+4
simplify parentheses:
![3 = a(1 {)}^(2) + 4](https://img.qammunity.org/2022/formulas/mathematics/college/2u0pay96rqrsmttt07o8j7f9r15qvyhkdf.png)
simplify exponent:
![3 = a + 4](https://img.qammunity.org/2022/formulas/mathematics/college/tkjapcsh1f4bftorkryjmizzg4sxyqu1s0.png)
therefore
![a = - 1](https://img.qammunity.org/2022/formulas/mathematics/college/ufsikpb545lhtlulfagrifor18zwa1thmg.png)
our vertex form of quadratic equation is
let's simplify it to standard form
simplify square:
![y = - ( {x}^(2) + 2x + 1) + 4](https://img.qammunity.org/2022/formulas/mathematics/college/9835xiasf6v8aqne37ob66myxua7ig955f.png)
simplify parentheses:
![y = - {x}^(2) - 2x - 1 + 4](https://img.qammunity.org/2022/formulas/mathematics/college/x2kkwp92bb2l6v2wmv61yt9n9nfi36zqo5.png)
simplify addition:
![y = - {x}^(2) - 2x + 3](https://img.qammunity.org/2022/formulas/mathematics/college/adtp3si4km8v2068q7at9sgvzdwqb1u14b.png)
therefore our answer is D)y=-x²-2x+3
the domain of the function
![x\in \mathbb{R}](https://img.qammunity.org/2022/formulas/mathematics/college/o7y4w13aem5kvhq0jr95yn3ne96ihy7r9y.png)
and the range of the function is
![y\leqslant 4](https://img.qammunity.org/2022/formulas/mathematics/college/zeongov9penl7wpzf0pv5cpyupvuy27b4y.png)
zeroes of the function:
![- {x}^(2) - 2x + 3 = 0](https://img.qammunity.org/2022/formulas/mathematics/college/yrfcdpooqydqs53jfnh2l6bdn02ldt8sna.png)
![\sf divide \: both \: sides \: by \: - 1](https://img.qammunity.org/2022/formulas/mathematics/college/ae6xdimqpez0a5n72vfwwisd9trg8ng84f.png)
![{x}^(2) + 2x - 3 = 0](https://img.qammunity.org/2022/formulas/mathematics/college/5pnb9nvjht8xuufe56cekzi5cnx3yqljto.png)
![\implies \: {x}^(2) + 3x - x + 3 = 0](https://img.qammunity.org/2022/formulas/mathematics/college/qqq5qwkmul742s6swlml5z777dj69d6gco.png)
factor out x and -1 respectively:
![\sf \implies \: x(x + 3) - 1(x + 3 )= 0](https://img.qammunity.org/2022/formulas/mathematics/college/p7d6mx0lplwoml0xvahtg8nnfy74thnezh.png)
group:
![\implies \: (x - 1)(x + 3) = 0](https://img.qammunity.org/2022/formulas/mathematics/college/zz4cd4c4s778kflu75ea3ompadz40cqe66.png)
therefore
![\begin{cases} x_(1) = 1 \\ x_(2) = - 3\end{cases}](https://img.qammunity.org/2022/formulas/mathematics/college/hv64rk6127ehfm3dcd33364cek98iugegx.png)